2019
DOI: 10.5115/acb.19.062
|View full text |Cite
|
Sign up to set email alerts
|

A cadaveric study of ovarian veins: variations, measurements and clinical significance

Abstract: The literature showing information regarding ovarian venous variation, its diameter and termination distance from respective renal venous origin are limited. This information is important in various surgical and clinical procedures including venous embolization, vascular reconstruction during renal transplantation and localizing the source of origin of a pelvic mass. We examined 94 sides of 47 formalin fixed female cadavers and noted the course and termination of ovarian veins. We measured the diameter of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In other reports [ 12 , 13 ] a customized gonadal vein graft was used similarly because the original diameter of the gonadal vein might be insufficient for reconstructing the SMV. Considering that a study of cadaveric ovarian veins showed an average diameter of 3.93 ± 1.11 mm [ 14 ], customization of an ovarian vein graft usually would be required for use in SMV reconstruction. In our case, using an ovarian vein showing preexisting dilation eliminated any need for customizing the graft and also was hoped to decrease the likelihood of future re-emergence of pelvic congestion symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other reports [ 12 , 13 ] a customized gonadal vein graft was used similarly because the original diameter of the gonadal vein might be insufficient for reconstructing the SMV. Considering that a study of cadaveric ovarian veins showed an average diameter of 3.93 ± 1.11 mm [ 14 ], customization of an ovarian vein graft usually would be required for use in SMV reconstruction. In our case, using an ovarian vein showing preexisting dilation eliminated any need for customizing the graft and also was hoped to decrease the likelihood of future re-emergence of pelvic congestion symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian veins follow a caudal-rostral retroperitoneal course parallel with the spinal column until they drain into the renal vein on the left and into the inferior vena cava on the right, representing only a part of the complex venous network related to the female pelvis. In the study of cadaveric ovarian veins mentioned above with respect to their diameters, mean distances of the termination points of the right and left ovarian veins from the confluences of the right and left renal veins with the IVC were 28.12 ± 7.54 mm and 28.49 ± 5.76 mm, respectively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported a single case with a duplicated LOV. The three variations of the OVs were unilateral [105]. Benedetti-Panici et al reported incidence of 2.2% for the LOV entering the lumbar vein.…”
Section: Ovarian Veins Anatomymentioning
confidence: 94%
“…Vessel variations in the paraaortic region and their clinical significance in Gynecologic Oncology are summarized in Table 1 [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][100][101][102][103][104][105][106]110].…”
Section: Preventing Iatrogenic Injury Of Variant Vesselsmentioning
confidence: 99%
“…The ovarian veins originate from the pampiniform plexus surrounding the ovaries. The ovarian veins travel from this plexus in the mesovarium and the broad ligament between the ovary and uterine tube [ 1 - 4 ]. Alongside the ovarian arteries, the ovarian veins ascend through the suspensory ligament (infundibulopelvic) and are positioned anterior to the psoas major muscle [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%